Surgical Diseases Management during COVID-19 Crisis at a Tertiary Care Hospital of India: Our Institutional Strategy - Singh, Sudhir Kumar; Gupta, Amit; Sandhu, Harindra; Mani, Rishit; Sharma, Jyoti; Kumar, Praveen; Rajput, Deepak; Kumar, Navin; Huda, Farhanul; Basu, Som Prakas; Ravi, Bina; Kant, Ravi (The Surgery Journal, 2021)
Introduction In response to the national coronavirus disease 2019 (COVID-19) pandemic, all hospitals and medical institutes gave priority to COVID-19 screening and to the management of patients who required hospitalization for COVID-19 infection. Surgical departments postponed all elective operative procedures and provided only essential surgical care to patients who presented with acute surgical conditions or suspected malignancy. Ample literature has emerged during this pandemic regarding the guidelines for safe surgical care. We report our experience during the lockdown period including the surgical procedures performed, the perioperative care provided, and the specific precautions implemented in response to the COVID-19 crisis.Materials and Methods We extracted patient clinical data from the medical records of all surgical patients admitted to our tertiary care hospital between the March 24th, 2020 and May 31st, 2020. Data collected included: patient demographics, surgical diagnoses, surgical procedures, nonoperative management, and patient outcomes.Results Seventy-seven patients were included in this report: 23 patients were managed medically, 28 patients underwent a radiologic intervention, and 23 patients required an operative procedure. In total eight of the 77 patients died due to ongoing sepsis, multiorgan failure, or advanced malignancy.Conclusion During the COVID-19 lockdown period, our surgical team performed many lifesaving surgical procedures and appropriately selected cancer operations. We implemented and standardized essential perioperative measures to reduce the spread of COVID-19 infection. When the lockdown measures were phased out a large number of patients remained in need of delayed elective and semi-elective operative treatment. Hospitals, medical institutes, and surgical leadership must adjust their priorities, foster stewardship of limited surgical care resources, and rapidly implement effective strategies to assure perioperative safety for both patients and operating room staff during periods of crisis.
Keywords: COVID-19; pandemic; elective; emergency; surgery